Titanium dioxide powder prepared by a sol-gel method - Pookmanee P. (2014)
Titanium dioxide (TiO2) powder was prepared by a sol-gel method. Titanium isopropoxide (Ti(OCH(CH3)2)4) and citric acid ((C3H5O(COO)3)H3-H 2O) were used as the starting precursors with a mole ratio of 1: 3. Ammonium hydroxide (NH4OH) was added to adjust the pH of the mixed final solutions. Co-precipitation powder was obtained with the final solutions at pH = 2, 4 and 6. The powder was dried at 80 °C for 24 h and calcined at 400 and 800 °C for 2 h with a heating rate of 5 Kminute"1. The phase transformation was investigated by an X-ray diffractometer (XRD). The anatase structure of titanium dioxide was obtained after calcination at 400 and 800 °C for 2 h. The microstructure was characterized by a scanning electron microscope (SEM). The range of particle size was 0.1-0.5 um with an irregular particle shape.